Efektivitas Sistem E-Court Terhadap Penyelesaian Perkara Perdata di Pengadilan Negeri Kabupaten Madiun - Alfina Haiba Mustafa; Hariyo Sulistyantoro (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
The effectiveness of the E-Court system in resolving civil cases at the Madiun Regency District Court is still not effective because there are several stages of the E-Court that have not been implemented optimally, for example related to the medition stage, evidence stage and decision stage. The problem with the E-Court system for registrants is dealing with the system or human error. Based on these obstacles, efforts have been made to overcome them, namely collaborating with the IT staff of the Madiun Regency District Court, establishing good communication, preparing everything and increasing human resources both by socializing the E-Court internally and externally. Therefore, the aim of this research is to determine the effectiveness of the E-Court system in resolving civil cases at the Madiun Regency District Court and the role of the Madiun Regency District Court in dealing with